Effects of redox modulation on postprandial oxy-inflammatory transcriptomic responses in overweight adults with cardiometabolic risk following a Mediterranean diet - Roberto Catanzaro; Leila Haghshenas; Ece Celik Atalay; Gulcin Sagdicoglu Celep; Aldo Lorenzetti; Reza Rastmanesh; Cristiana Aperio; Maki Osato; Joseph Cervi; Francesco Marotta (Eurasian Journal of Medicine and Oncology, 2026)
Introduction: The postprandial phase represents a transient pro-oxidative condition, characterized by an increased vulnerability to oxidative damage following nutrient intake. This state is increasingly recognized as a contributing factor in the early development of atherogenic processes. Alterations in plasma cysteine and glutathione (GSH) redox couples have been shown to correlate with aging and age-related pathologies. Among the principal thiol redox systems regulating plasma redox potential, the reduced cysteine/cystine (CySS) pair predominates, followed by the GSH/oxidized GSH disulfide pair. CySS is considered a marker of systemic oxidative burden, whereas GSH reflects intracellular NADPH-dependent reductive capacity. Objective: This study aimed to assess both intra- and extracellular redox status during the postprandial period in middle-aged and older sedentary individuals adhering to a Mediterranean dietary pattern, with or without supplementation using a patented fermented papaya preparation (FPP). Methods: A total of 90 otherwise healthy participants presenting at least one cardiometabolic risk factor were enrolled. Postprandial assessments were conducted at baseline and after three months. Evaluated parameters included inflammatory biomarkers, adhesion molecules, apoptosis in peripheral blood mononuclear cells, and p53 gene expression. Results: Compared with the Mediterranean diet alone, three months of FPP supplementation resulted in significant reductions in soluble levels of vascular cell adhesion molecule 1 and intercellular adhesion molecule 1. It also effectively prevented the postprandial increase in Annexin V⁺/DAPI⁺ cells and induced a protective downregulation of p53 expression, particularly within the cytoplasmic compartment. Furthermore, CySS concentrations and the CySS:GSH ratio were significantly reduced, while the decline in GSH levels was attenuated under the FPP-supplemented regimen. Conclusion: These findings support the potential benefit of dietary interventions, particularly when combined with redox-modulating nutraceuticals, in reducing postprandial oxidative stress and its associated metabolically deleterious effects.